THE INFLUENCES OF ACCRUALS QUALITY AND TAX MANAGEMENT ON THE FUTURE MARKET VALUE: CASE STUDY OF THE LISTED FIRM ON INDUSTRY MANUFACTURING SECTORS - Muljanto Siladjaja; Indra Siswanti; Syafrida Hafni Sahir (Management Research Studies Journal, 2021)
This empirical research has proven that the investor insisted on the management to level up the earnings quality constantly, there is no tolerance for any distortion, including the negative effect of opportunistic accruals. The high earning quality paves out the way for the investor to calculate the future return accurately, by minimizing the volatile movement of market price and agency cost. This research tested how the accruals quality and tax management influences the investor’s perception in the future, that measured by future market value. The observation data had used the samples on the listed company in the industrial manufacturing sector for the period 2015 until 2017, which had amounted to 384 observation data. This multiple regression model with data panel has used the discretionary accruals quality, tax management, and future market value, the result is the earnings quality has a positive influence on the future market value significantly. The management should carry out consistently all available tax accounting standards and tax regulations at the maximum level without any infringement, this one is related to deduct the risk. It is an implication of the Signalling and Regulation Theory. The investor has realized the gap between the accounting standard and tax regulation intolerance zone, absolutely it has no crucial impact on the volatile movement of the market price. Primarily they concern about the high book and tax accruals, meanwhile ignoring both positive or negative. Principally, the high-quality accounting information has a contribution to predicting the better-expected return accurately in the future period, this is aimed to protect the investment in the high safety area.